Organeleptic Test for Fortified Packaging Milk by Utilizing Calcium from Egg Shell Waste - Chandra Halim; Muhammad Fadli; Dicki Darmawan; Dwinta Nurul Fadillah Bintang; Farhan Rahmadani (Nusantara Scientific Medical, 2022)
In terms of national needs, the necessity for eggs reached 4,742,240 tons employing massive impact on the production of egg shell waste. Nevertheless, packaging milk released in the market contains low calcium and unsatisfies the nutritional needs of adult calcium, namely 1000 mg/day. Therefore, it is necessary to add waste of calcium-rich egg shells so the nutritional needs of calcium can be fulfilled and reduces the egg shell waste at the same time. The research method used is combination of experimental methods, interviews, and literature study. The data is analyzed by using descriptive statistics and non-parametric statistical tests to draw conclusions. Based on the data obtained, the best variation is the milk control with a total value of 580 points, 33 points different from 2:1 variation. The giving of egg shell waste reduces the milk aroma which is preferable for people who dislike its aroma. Through non-parametric statistical tests, it was investigated that there was no significant difference in adding egg shell flour to make fortified milk except for egg shell control. Therefore, egg shell flour can be used as additional material to enrich the calcium, to reduce the milk aroma and the amount of organic waste in Indonesia.